PERANCANGAN SISTEM INFORMASI KLAIM BPJS KESEHATAN RAWAT JALAN BERBASIS WEB DI RSUD KOJA JAKARTA UTARA - Ayu Purwasih, Dwi; Abdussalaam, Falaah (POLITEKNIK PIKSI GANESHA, 2024)
The technology and information that is very advanced, it can affect many aspects of the system in supporting service performance. Changing the manual system used previously more effectively. Completeness determines the claim at the hospital, the more complete the file will make the claim correct and of high quality. Medical records, especially the Casemix section, are units can present claim data information. The use of electronic claims(E-Claim) will facilitate the claim process through electronic files so as to reduce the use of excessive paper and will facilitate the search for claim files during verification and audit, and most importantly, it will minimize file printing costs. Based on observations at the Koja Regional General Hospital in processing and monitoring claims data, it is still in the form of manual recording using Ms. Excel and Google Spreedsheet. The objectives and benefits of Design of a Web-based Outpatient Health BPJS Claim Information System at RSUD Koja North Jakarta, among others:1. Supporting the processing of BPJS claim data, especially outpatients. 2. Can monitor the BPJS Health Outpatient claim file. The method used is a qualitative method with a descriptive approach. The web system makes it easier for users to do their work, anytime and anywhere can be accessed.